Problems In the Use of Water Resources in Our Republic and Ways to Overcome Them (Zien Journal of Social Sciences and Humanities, 2021)
Water resources due to the arid zone of the Republic unevenly distributed. Therefore, our country does not have enough water resources and requires rational use of water. Therefore, efficient use of water solves many problems. To do this, we need to use water-saving methods and find ways to use waste and wastewater more efficiently..